Comparing patient-reported outcomes across countries: An assessment of methodological challenges. Issue 3 (July 2021) - Sutherland, Jason M; Rajapakshe, Shanika; Crump, Trafford; Chartrand, Andrée; Liu, Guiping; Karimuddin, Ahmer
Objectives: There is little published literature on the comparison of patient-reported outcomes between countries. This study aimed to assess pre- and postoperative health among samples of patients undergoing elective groin hernia repair procedures in the National Health Service (NHS), England, and groin hernia patients in Vancouver, Canada. Methods: We used datasets from two different sources. For the English NHS we used published anonymized patient-level data files which include the EQ-5D(3L) patient-reported outcome measure and a number of demographic and clinical characteristics. For Vancouver, we used data from a sample of Vancouver patients who completed the same instrument during a similar time frame. English patients were matched with Vancouver participant's characteristics using propensity score methods. A linear regression model was used to measure differences in postoperative visual analogue scale values between countries, adjusting for patient characteristics. Results: Our study revealed a range of methodological issues concerning the comparability of patient-reported outcomes following hernia repair surgery in the two health systems. These related to differences in approaches to collecting patient-reported outcome measures and the nature of explanatory variables (self-report vs. administrative data), among other challenges. As a consequence, there were differences between the matched samples and the NHS data, indicating a healthy participant bias. Unadjusted results found that Vancouver patients (N = 280) reported more problems in domains of mobility, self care, usual activities and anxiety/depression than the matched cohort of NHS patients (N = 840). Interpreting differences is challenging given different sampling designs. Conclusions: There are significant hurdles facing comparisons of surgical patients' outcomes between countries, including adjusting for patient differences, health system factors and approaches to survey administration. While between-country comparisons of surgical outcomes using patient-reported outcomes shows significant promise, much work on standardizing sampling design, variables and analytic methods is needed.